A SUCUMBÊNCIA DA FAZENDA PÚBLICA NA EXECUÇÃO FISCAL E A OBRIGATORIEDADE DO RESSARCIMENTO DOS CUSTOS DO EXECUTADO COM A MANUTENÇÃO DO SEGURO-GARANTIA OU DA FIANÇA BANCÁRIA / THE LOSS OF THE TAX AUTHORITIES IN TAX EXECUTION PROCEDURES AND THE DUTY TO REIMBURSE THE COSTS OF EXPENSES MADE BY THE TAXPAYER TO GUARANTEE THE LAWSUIT WITH INSURANCE OR BANK GUARANTEES - Lisboa, Julcira Maria de Mello Vianna (2022)
Resumo: O presente artigo visou analisar se a Fazenda Pública sucumbente deve ser condenada a ressarcir ao executado vencedor as despesas que este teve com a contratação e manutenção de seguro-garantia ou fiança bancária em execução fiscal. Para tanto, mediante pesquisa jurisprudencial, buscou-se identificar não só quais as normas de direito positivo aplicáveis ao tema, mas, principalmente, como essas normas vêm sendo interpretadas e aplicadas pelo Poder Judiciário, bem como quais são os argumentos jurídicos que vêm sendo apresentados pelos contribuintes e pelas Fazenda Públicas em sua defesa. A partir do resultado dessa pesquisa, que demonstrou que o argumento central da discussão é se a contratação dessas garantias é ou não uma liberalidade do executado, o artigo buscou analisá-lo mediante interpretação sistemática do direito positivo, bem como em elementos da filosofia do direito. A conclusão dessa análise foi a de que a despeito de a contratação dessas espécies de garantia ser uma liberalidade do contribuinte, ela deve ser objeto de ressarcimento por parte da Fazenda Pública sucumbente.Palavras-chave: Execução fiscal. Despesas processuais. Seguro-garantia. Fiança bancária. Reembolso. Abstract: This article aimed to analyze if the taxpayer who wins a tax execution procedure has the right to be reimbursed by the tax authorities of the expenses with insurance or bank guarantees made to guarantee the lawsuit. The first step of this analysis was a research on precedents, whose result have shown not only the rules applicable to the case but, mainly, how these rules are being interpreted and applied by the Brazilian Courts and which are the main arguments used by the taxpayers and by the tax authorities. The conclusion of this research was that the main point of doubt is whether these expenses are at the taxpayer will or not, considering that there are other ways to guarantee the tax execution procedures, such as the cash deposit of the values being disputed in an official bank account or the attachment of any other of the taxpayer goods. Therefore, the article analyzed the matter from a systematic interpretation of the rules in the Tax Execution Procedure Law, the Civil Procedure Law and considering elements of philosophy of law. The conclusion of this study was that although the hiring of insurance or bank guarantee is a choice of the taxpayer, it shall be reimbursed by the tax authorities in case they lose a tax execution procedure.Keywords: Tax execution procedure. Legal costs. Insurance or bank guarantee. Reimburse.